Life cycle assessment of heat, CO2 from composting for greenhouse applications - Jiamin Wang; BiChen Tian; Rui Li; Jianming Li (Journal of CO2 Utilization)
Greenhouses play a crucial role in agricultural production, especially in high-latitude regions requiring supplemental heating during winter. This study explores the potential of a Shed-type Greenhouse Composting Device (SGCD) to recover heat and CO2 from composting agricultural waste (AW) for use in solar greenhouses. A Life Cycle Assessment (LCA) was conducted to evaluate the environmental impacts of the SGCD system, covering its construction, operation, and recycling units. The results show that heat and CO2 recovery significantly reduce reliance on coal heating and CO2 cylinders, with heat recovery contributing 30.94 % and CO2 recovery 17.40 % to impact reduction. Key environmental hotspots include the impacts of construction materials, water, electricity, and diesel use. Sensitivity analysis revealed that the system is most sensitive to freshwater ecotoxicity, toxicity equivalent, and marine ecotoxicity. The impact of AW processing is minimal, contributing only 1.09 % of the total impact. Economically, the SGCD system increases tomato yield by 15.06 %, generating an additional $225.35 in annual revenue, with a payback period of two years and profitability from the third year. Overall, the SGCD system offers both environmental and economic benefits, promoting energy-efficient, low-carbon agricultural practices in high-latitude greenhouses.